PERLINDUNGAN HUKUM TERHADAP PEKERJA WANITA PADA PT TOTALINDO BANGGAI PERKASA - SRI WAHYUNI; NIRWAN MOH. NUR; RISNO MINA (Jurnal Yustisiabel, 2019)
This research aims to examine the implementation of the legal protection of female workers at PT Totalindo Perkasa, Banggai and the factors that affect its implementation. Research methods used are empirical juridical research with qualitative, descriptive methods of analysis. The conclusion that the implementation of the legal protection of women workers of PT Totalindo Perkasa Banggai, namely: women workers wage Protection, protection, protection of leave annual breaks, long breaks, protection protection in the exercise of worship, work safety and health protection. While the factors that affect the actors implementing legal protection of women workers at the PT Banggai Mighty Totalindo, consisting of an inhibitor factor and factor endowments. The supporting factor is a factor of laws in the field of Employment law, while restricting factor is the factor less workers understand the rights of women workers who should be protected.